2021
DOI: 10.1021/acsapm.1c00765
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Nanocrystals Influence Polyamide 6 Crystal Structure, Spherulite Uniformity, and Mechanical Performance of Nanocomposite Films

Abstract: Cellulose nanocrystals (CNCs) are an ideal reinforcing agent for polymer nanocomposites. CNCs can form hydrogen bonds with polyamide 6 (PA6); however, the direct effects of unmodified CNCs on PA6 morphology and crystal structure have not been fully elucidated. This work investigated the influence of CNCs on the mechanical performance and physicochemical properties of spin-coated CNC−PA6 films through quantitative analysis using techniques that probe multiple length scales. CNCs interacted with PA6 to induce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…For instance, the conventional models predict a linear or exponential increase in elastic modulus of composites with respect to the concentration of fillers; however, experimental observations indicate that the elastic modulus of nanocomposites reaches a plateau value or decreases with increasing loading. [19][20][21][22][23] It is often observed that conventional models predict the elastic modulus at very low concentrations and often diverge from experimental findings as nanofiller concentration increases. 19,[24][25][26] Consideration of the individual state of agglomerates is necessary for accurate predictions at high concentrations, which can be achieved by combining the continuum-based models and statistical approaches.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the conventional models predict a linear or exponential increase in elastic modulus of composites with respect to the concentration of fillers; however, experimental observations indicate that the elastic modulus of nanocomposites reaches a plateau value or decreases with increasing loading. [19][20][21][22][23] It is often observed that conventional models predict the elastic modulus at very low concentrations and often diverge from experimental findings as nanofiller concentration increases. 19,[24][25][26] Consideration of the individual state of agglomerates is necessary for accurate predictions at high concentrations, which can be achieved by combining the continuum-based models and statistical approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of MMT (4.7 wt.%) resulted in an increase in the tensile strength of these composites from 69 to 97 MPa and in their tensile modulus from 1.1 to 1.9 GPa. The use of cellulose nanocrystals (CNCs) [ 8 , 9 , 10 , 11 , 12 ] and cellulose nanofibers (CNFs) [ 8 , 13 , 14 , 15 ] as reinforcements for polymer composites have also been studied in PA6.…”
Section: Introductionmentioning
confidence: 99%
“…The main challenge in their processing is associated with an effective dispersion and distribution of the cellulose nanomaterials in the polymer matrix, owing to their tendency to agglomerate and their thermal instability at temperatures above 200 °C [ 16 ]. To overcome these challenges, high-energy processes [ 11 , 13 ], and chemical modifications [ 12 , 15 , 16 ] have been used. For example, ball-milling and cryo-milling [ 11 ] were used to produce the polymer and cellulose in powder form to facilitate the mixing and dispersion of cellulose with PA6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spin-coating has been used to produce modified CNC reinforced polylactic acid (PLA) thin films. 24 In the case of PA6, our previous study is the only research in which this technique was used to produce CNC reinforced PA6 thin films 25 ; however, spin-coated modified CNC reinforced PA6 films have not been investigated in the literature. Numerous pathways have been followed to modify CNC.…”
Section: Introductionmentioning
confidence: 99%